Facilitating genuine community participation: can development learn from design?. Issue 1 (1st January 2021) - Flint, Adrian; Blyth, Simon
ABSTRACT: Despite decades of debate with respect to facilitating 'bottom up' solutions and increased 'beneficiary participation' in development, there is little evidence to suggest genuine intellectual exchange between donors and 'beneficiaries'. Nearly seven decades have witnessed only relatively minor shifts in established power hierarchies, and the sector remains one dominated largely by 'top-down' approaches to decision-making. This paper posits that development, as both a concept and a practice, could be enriched significantly if academics and practitioners paid closer attention to the participatory aspects of design methodologies. While design is associated largely with commercial activity, in the hands of more radical designers its methods can be used to generate more participatory ways of thinking and 'doing'. With this in mind, we consider the extent to which, by employing aspects of design methodologies, there might be scope for alternative approaches to the ways in which development is conceived and practised.